Effect Of The Drug Miopets On Body Weight And Clinical And Physiological Indicators Of Retarded Growth Rabbits - Yunusov H.B; Bio.ph.d Niyozov H.B; Eshkuvatov Kh.Kh; Assistant, (PhD), S.B. Abdiev; Pardaeva Sh.A; B. Kokilov Doctoral Student; A. Ruziev Doctoral student; Tojiddinov I. master's (Genius Publishing Group, 2025)
This article describes the results of using antiparasitic drugs in combination with gamma globulin in stunted and weakened rabbits. With parenteral administration of gamma globulin at a dose of 1 ml per 1 kg of live weight, as well as the immunomodulator Miopets— for the first time at a dose of 1 ml and again after 10 days also at a dose of 1 ml intramuscularly — positive changes were observed in the rabbits by the 20th day: free movement, improved growth and development. By the end of the experiment, the body weight of the rabbits reached 4.800±0.42 kg, which is on average 2100 g more than at the beginning of the experiment and 950 g more than the control group. It was also established that with parenteral administration of gamma globulin at a dose of 1 ml per 1 kg of live weight in combination with antiparasitic agents in stunted and weakened rabbits, by the 30th day of the experiment an improvement in growth and development was observed, and the body weight at the end of the experiment was 3.150 ± 0.33 kg, which is 1150 g more than at the beginning of the experiment.
Keywords: hypotrophy; gamma globulin; parenteral; symptomatic